PENERAPAN STRATEGI KOOPERATIF TIPE TWO STAY TWO STRAY DENGAN MENGGUNAKAN METODE PEMECAHAN MASALAH DALAM PEMBELAJARAN BIOLOGI KELAS XI IPA SMAN 7 PADANG - Pratiwi, Anesti; Fitri, Dwi Rini Kurnia; Zulmardi, Zulmardi (Jurnal Pembelajaran MIPA, 2014)
Purpose of this research is to find out studentsâ learning outcome of biology subject in applying cooperative strategy type two stay two stray by use of problem solving method for students in class XI sains SMAN 7 Padang. Kind of this research is pseudo experimental research in randomized control group only design. There are three phase of the research procedure, namely: pre-operation, operation and post operation. The research instrument of this research is achievement test. There are some phase to design this instrument test, first, creating the test, doing validation testing, doing try out, and analyzing the question. Technique of data analysis is normality testing, homogeneity testing, and hypothesis testing. The finding of this research shows that there are differences of mean score, deviation standard, and variants between experimental class and control class. It shows that studentsâ learning outcome in experimental class that applying cooperative strategy type two stay two stray by use of problem solving method is better than control class. Key words: cooperative strategy type two stay two stray, problem solving method, biology subject